The last days according to Jesus - Sproul, Robert Charles, 1939- (Grand Rapids, MI Baker, 1999)
Includes bibliographical references and indexes.
Keywords: Second advent -- Biblical teaching; Jesus Christ -- Prophecies; Bible. N.T. Prophecies -- second advent